(untitled) (American Journal of Islam and Society, 2011)
is an interesting and informative study of urban Malay women who have turned to Islam to regulate their daily lives. While the book focuses on Muslim women, it is written for a broader audience not necessarily familiar with Islam—namely, anthropologists and feminists. Following Saba Mahmoud1 and other recent scholarship on pious Muslim women, Frisk argues for the necessity of acknowledging agency not only when it resists or reinforces patriarchy. Much of feminist writing has recognized women’s agency only when women have actively resisted patriarchy. Otherwise, women are seen as passive victims. Frisk critiques this dichotomous understanding of agency. The aim of Submitting to God is thus to treat pious women as agents and to understand the meaning of what they do as defined by the women themselves (5). Instead of focusing on the effects of Islamization on women’s lives, the book’s goal is to account for women’s Islamization—that is, their religiosity and their spiritual development (15). Frisk conducted her fieldwork from 1995 to the present in mosques in Kuala Lumpur’s affluent ...